Detection and Persistence of Vi Antigen in Tissues of Actively Immunized Mice - Gaines, Sidney (1965)
Gaines, Sidney (Walter Reed Army Institute of Research, Washington, D.C.), Julius A. Currie, and Joseph G. Tully. Detection and persistence of Vi antigen in tissues of actively immunized mice. J. Bacteriol. 89:776–781. 1965.—The presence, distribution, and persistence of Vi antigen in mouse tissue was determined by means of active immunization tests with tissue extracts. Mice were injected intraperitoneally with purified Vi antigen or Vi-containing bacilli. At appropriate intervals, animals were killed, and saline extracts of their tissues were prepared. Mice were immunized with these extracts and challenged 6 days later with 10 ld(50) of Salmonella typhosa Ty2. Protection was afforded by tissue extracts from Vi-injected mice, but not by normal tissue extracts. That the immunizing capacity of tissue extracts from Vi-injected mice was attributable to Vi antigen was affirmed by the demonstration that these extracts stimulated the production of Vi antibody in mice, coated erythrocytes for agglutination by Vi antiserum, and inhibited agglutination of Vi-sensitized red blood cells by known Vi antisera. Vi antigen could be detected in the liver and spleen of mice injected with as little as 1 μg. In mice given 150 μg, the antigen was still present in liver tissue 231 days later.